Clinical and electrophysiological impact of repetitive low-frequency transcranial magnetic stimulation on the sensory–motor network in patients with restless legs syndrome. (23rd February 2018) - Lanza, Giuseppe; Cantone, Mariagiovanna; Aricò, Debora; Lanuzza, Bartolo; Cosentino, Filomena Irene Ilaria; Paci, Domenico; Papotto, Maurizio; Pennisi, Manuela; Bella, Rita; Pennisi, Giovanni; Paulus, Walter; Ferri, Raffaele
Background: Based on the hyperexcitability and disinhibition observed in patients with restless legs syndrome (RLS) following transcranial magnetic stimulation (TMS), we conducted a study with low-frequency repetitive TMS (rTMS) over the primary motor (M1) and somatosensory cortical areas (S1) in patients with RLS. Methods: A total of 13 right-handed patients and 10 age-matched controls were studied using clinical scales and TMS. Measurements included resting motor threshold (rMT), motor-evoked potentials (MEPs), cortical silent period (CSP), and central motor conduction time (CMCT). A single evening session of rTMS (1 Hz, 20 trains, 50 stimuli each) was administered over the left M1, left S1, and sham stimulation over M1 in a random order. Clinical and TMS measures were repeated after each stimulation modality. Results: Baseline CSP was shorter in patients than in controls and remained shorter in patients for both motor and somatosensory stimulation. The patients reported a subjective improvement of both initiating and maintaining sleep the night after the rTMS over S1. Patients exhibited a decrease in rMT after rTMS of S1 only, although the effect was smaller than in controls. MEP latency and CMCT changed only in controls after stimulation. Sham stimulation was without effect on the observed variables. Conclusions: rTMS on S1-M1 connectivity alleviated the sensory–motor complaints of RLS patients. The TMS indexes of excitation and inhibition indicate an intracortical and corticospinal imbalance, mainly involving gamma-aminobutyric acid (GABA)ergic and glutamatergic circuitries, as well as an impairment of the short-term mechanisms of cortical plasticity. The rTMS-induced activation of the dorsal striatum with the consequent increase of dopamine release may have contributed to the clinical and neurophysiological outcome.